2018
DOI: 10.1108/gkmc-11-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Use of social media by social science academics for scholarly communication

Abstract: Purpose The purpose of this study is to investigate social science academics’ use of social media for scholarly communication at Kuwait University. Design/methodology/approach Phase One data were collected through web-based and paper responses to questionnaires. Faculty members, teachers and teaching assistants in the social science faculty were invited to participate. Forty-six of the 100 invited participants responded. Phase Two comprised interviews with 10 respondents. Findings Social connection platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
(38 reference statements)
4
33
0
2
Order By: Relevance
“…**p < .01. progression-encouraged academics to direct their attention toward professional SNSs. Nonetheless, the present results also revealed that the usage of SNSs for personal purposes outweighed their usage for work purposes, which was not surprising, since it matches the findings of prior studies conducted with various samples, including the United States, Italy, and the Middle East (Al-Daihani et al, 2018;S. Manca & Ranieri, 2016a;Moran et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…**p < .01. progression-encouraged academics to direct their attention toward professional SNSs. Nonetheless, the present results also revealed that the usage of SNSs for personal purposes outweighed their usage for work purposes, which was not surprising, since it matches the findings of prior studies conducted with various samples, including the United States, Italy, and the Middle East (Al-Daihani et al, 2018;S. Manca & Ranieri, 2016a;Moran et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The benefits of utilizing social networking when carrying out research are quite clear. Consistent results across studies have revealed that social media sites provide a convenient environment for scholarly communication and research dissemination (Al-Daihani et al, 2018;Gu & Widén-Wulff, 2011;S. Manca & Ranieri, 2017a).…”
Section: Social Mediamentioning
confidence: 63%
See 1 more Smart Citation
“…The more individuals find others with similar characteristics in terms of vision and values, the higher the frequency of interaction (Al‐Daihani, Al‐Qallaf, & AlSaheeb, ). Thus, individuals with similar objectives are expected to have higher levels of interactions than those who do not.…”
Section: Research Model and Hypothesis Formulationmentioning
confidence: 99%
“…For example, Lecturers often use Blogs, Skype, Wikis, Facebook; and even mobile apps, such as WhatsApp in distance learning in University (Mnkandla & Minnaar, 2017;Owusu-Ansah, Gontshi, Mutibwa, & Ukwuoma, 2015;Callaghan & Fribbance, 2016;Hussain, Cakir, & Candeger, 2018). The most common use of social media includes searching and studying in collaborative online activities, download media, sharing information, and entertainment (Wheeler, Yeomans, & Wheeler, 2008;Al-Daihani, Jumanah, & Sara, 2018). In teacher education, teacher educator used social media for motivating teacher candidate to collaborate with a cooperative teacher or mentor; providing a friendly atmosphere to encourage reflection to identify and address challenges of teaching practice; giving feedback and continue following up on their progress in teaching practice (Pitiporntapin & Lankford, 2015).…”
Section: Introductionmentioning
confidence: 99%